HEALTH WORKERS PERCEPTION OF SOCIAL MEDIA AS A TOOL FOR PROMOTING NUTRITION BEHAVIOURS AMONG PREGNANT WOMEN IN SABO TASHA COMMUNITY - JAMILA MUSA; AYODELE BABATUNDE JOSEPH (International Studies Journal)
This study focuses on the perception of health workers in the Sabo Tasha community regarding the use of social media as a tool for promoting nutrition behaviours among pregnant women. The research objectives of this study are to assess the perception of health workers in the Sabo Tasha community regarding the use of social media for promoting nutrition behaviours among pregnant women and to identify potential barriers to its use. The review of concepts provides an understanding of social media, nutrition behaviours, and the role of health workers in promoting and maintaining health. The paper was anchored on social cognitive theory and secondary data approach was used to collect data from a variety of sources, including reports, articles, online news and websites, journals. The study revealed that health workers in the Sabo Tasha community have varying perceptions of social media as a tool for promoting nutrition behaviours among pregnant women. Some health workers recognize the potential of social media and perceive it as a valuable platform for reaching and engaging with pregnant women. The paper concluded there is different perception of health workers in the Sabo Tasha community regarding the use of social media as a tool for promoting nutrition behaviours among pregnant women. The paper recommended that Health workers should be provided with appropriate training and capacity building programs to enhance their digital literacy skills and knowledge of social media platforms.